ZAKIAH DARADJAT DAN PEMIKIRANNYA TENTANG PERAN PENDIDIKAN ISLAM DALAM KESEHATAN MENTAL - Mawangir, Mawangir (Intizar, 2015)
AbstractThis paper is a research result that discusses the thoughts of Zakiah Daradjat about the role of Islamic education on mental health. Education in his perspective includes human life that is not only focused on the aspects of faith or morality, but much broader and deeper than it all. Understanding mental health related to the potential of men refers to the establishment of a genuine harmony between the functions of the soul and ability to deal with common problems and avoid the anxiety. Therefore, this paper concludes that Zakiahâs thoughts about the role of Islamic education on mental health can guide, help and control in morality and mental disorders.Â Keywords: Islamic education, mental healthÂ